Review of Charles E. SNYDER, Beyond Hellenistic Epistemology. Arcesilaus and the Destruction of Stoic Metaphysics - Rover, Chiara (Ciceroniana On Line, 2024)
Review uf Charles E. SNYDER, Beyond Hellenistic Epistemology. Arcesilaus and the Destruction of Stoic Metaphysics, Bloomsbury, London-New York 2021, 224 pp., ISBN 9781350202382.